Sex Hormone Receptor Repertoire in Breast Cancer - Gerald M. Higa; Ryan G. Fell (International Journal of Breast Cancer)
Classification of breast cancer as endocrine sensitive, hormone dependent, or estrogen receptor (ER) positive refers singularly to ERα. One of the oldest recognized tumor targets, disruption of ERα-mediated signaling, is believed to be the mechanistic mode of action for all hormonal interventions used in treating this disease. Whereas ERα is widely accepted as the single most important predictive factor (for response to endocrine therapy), the presence of the receptor in tumor cells is also of prognostic value. Even though the clinical relevance of the two other sex hormone receptors, namely, ERβ and the androgen receptor remains unclear, two discordant phenomena observed in hormone-dependent breast cancers could be causally related to ERβ-mediated effects and androgenic actions. Nonetheless, our understanding of regulatory molecules and resistance mechanisms remains incomplete, further compromising our ability to develop novel therapeutic strategies that could improve disease outcomes. This review focuses on the receptor-mediated actions of the sex hormones in breast cancer.